2010
DOI: 10.1021/mp100175a
|View full text |Cite
|
Sign up to set email alerts
|

High-Permeability Criterion for BCS Classification: Segmental/pH Dependent Permeability Considerations

Abstract: The FDA classifies a drug substance as high-permeability when the fraction of dose absorbed (F(abs)) in humans is 90% or higher. This direct correlation between human permeability and F(abs) has been recently controversial, since the β-blocker sotalol showed high F(abs) (90%) and low Caco-2 permeability. The purpose of this study was to investigate the scientific basis for this disparity between permeability and F(abs). The effective permeabilities (P(eff)) of sotalol and metoprolol, a FDA standard for the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 44 publications
4
91
0
Order By: Relevance
“…unstirred water layer (UWL) permeation, transcellular permeation, paracellular permeation and/or carried-mediated absorption/efflux (2,(17)(18)(19). In addition, jejunal P eff can be affected by the experimental conditions and the physiological factors that the drug might encounter during its passage through the intestinal membrane in the upper jejunum (3,12,20).…”
Section: Introductionmentioning
confidence: 99%
“…unstirred water layer (UWL) permeation, transcellular permeation, paracellular permeation and/or carried-mediated absorption/efflux (2,(17)(18)(19). In addition, jejunal P eff can be affected by the experimental conditions and the physiological factors that the drug might encounter during its passage through the intestinal membrane in the upper jejunum (3,12,20).…”
Section: Introductionmentioning
confidence: 99%
“…Pseudoephedrine hence represents a case of disagreement between the BCS and the BDDCS, and a deviation from the P eff -F met (fraction metabolized) correlation proposed by the BDDCS. Thus, while the extent of drug metabolism may be useful in supporting permeability classification under certain circumstances, the data presented in this paper demonstrate the care that must be taken with intestinal permeability/extent of absorption determinations (12,24,44).…”
Section: Discussionmentioning
confidence: 79%
“…5), and by previous reported studies ( [41][42][43]. The increasing pH along the intestine may result in this unique absorption pattern for a whole class of molecular entities; we have previously shown that the β-blocker sotalol follows a similar permeability pattern, starting as lowpermeability in the proximal GI sections, increasing gradually with the pH increase throughout the small intestine, and becomes a high-permeability compound as the pH rises above 7.5 in the ileum, which allows for complete absorption of this drug (24). While pseudoephedrine includes the basic secondary amine as a sole ionizable center, sotalol is an amphoteric molecule that contains the acidic methanesulfonamide functionality and the basic secondary amine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor that may influence the apparent permeability of the drug compounds is the relation between the drugs pKa values and the pH of the different media. One has thus to consider that the intestinal permeability along the GI tract could be pH dependent, since pH might influence the drugs' charge state, and further affect the drug absorption in a more complex manner (Dahan et al, 2010;Lennernäs, 2014).…”
Section: Influence Of Fassif and Fessif On Permeability Of Drugsmentioning
confidence: 99%